LONELINESS AND RISK OF DEMENTIA. (16th November 2018) - Sutin, A; Stephan, Y; Luchetti, M; Terracciano, A
Abstract: Social isolation is a risk factor for dementia. The published literature is mixed for loneliness, a subjective component of isolation that overlaps but is independent of degree of social contact. The present study tests whether loneliness is associated with risk of dementia in the largest sample to date and further examines whether the association varies by demographic factors and genetic vulnerability. Participants from the Health and Retirement Study (N=12, 030) reported on their loneliness, social isolation, and had information on clinical, behavioral, and genetic risk factors. Cognitive status was assessed at baseline and every two years over a 10-year follow-up with the modified Telephone Interview for Cognitive Status (TICSm). A TICSm score of 6 or less was indicative of dementia. Cox proportional hazards regression indicated that loneliness was associated with a 40% increased risk of dementia. This association held controlling for social isolation, and clinical, behavioral, and genetic risk factors. The association was similar across gender, race, ethnicity, education, and genetic risk. Loneliness is associated with increased risk of dementia. It is one modifiable factor that can be intervened on to reduce dementia risk.